(untitled) (Journal of Economic Research & Business Administration, 2016)
At the present stage of development of the Kazakhstan economy over-all performance of the organizations depends on the applied technologies and system of management more and more. Controlling, providing stability of business and its finance, revealing internal reserves and quickly intro-ducing innovations, acts as an important factor of ensuring competitive-ness of the company. In modern conditions actual is a development of the mechanism of the organization of the controlling allowing to approach in a complex a question of creation of system of controlling at the enterprise.